2018
DOI: 10.1002/jmri.26167
|View full text |Cite
|
Sign up to set email alerts
|

Children with kawasaki disease present elevated stiffness of great arteries: Phase‐contrast MRI study

Abstract: Patients with KD have elevated great vessel stiffness measured at the chronic stage of the disease. Accelerated stiffness process does not appear to affect biventricular function in youth Level of Evidence: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;47:1228-1236.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Increase in stiffness of aorta and decrease in elasticity has also been reported by several authors leading to functional impairment of aorta. This has been observed both during the acute stage and several years after the diagnosis of KD ( 104 106 ).…”
Section: Aortic Root Involvementmentioning
confidence: 90%
“…Increase in stiffness of aorta and decrease in elasticity has also been reported by several authors leading to functional impairment of aorta. This has been observed both during the acute stage and several years after the diagnosis of KD ( 104 106 ).…”
Section: Aortic Root Involvementmentioning
confidence: 90%
“…sCD40L can interact with CD40 present on a variety of cells in the blood vessels leading to inflammation and an atherogenic potential 10–19 . It has been postulated that KD may have long-term cardiovascular sequelae even when there have been no overt CAA during acute stage 20–31 . Although there are several differences in the pathogenesis of KD vasculopathy and atherosclerotic heart disease, several studies have also shown that patients with KD have an increased risk of premature atherosclerosis as assessed using flow-mediated dilatation of brachial artery or carotid intima media thickness 19–33 .…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19] It has been postulated that KD may have long-term cardiovascular sequelae even when there have been no overt CAA during acute stage. [20][21][22][23][24][25][26][27][28][29][30][31] Although there are several differences in the pathogenesis of KD vasculopathy and atherosclerotic heart disease, several studies have also shown that patients with KD have an increased risk of premature atherosclerosis as assessed using flow-mediated dilatation of brachial artery or carotid intima media thickness. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] Long-term vasculopathy in patients with KD is characterized by chronic inflammation, endothelial dysfunction, luminal fibroblast proliferation, and thrombosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation